WORKING WITH CHILDREN WITH AUTISM SPECTRUM DISORDER IN INCLUSIVE CONDITIONS (Web of Teachers: Inderscience Research, 2023)
The article presents theoretical and practical aspects of organizing the education of children with autism syndrome in the inclusive education system. At the same time, the communication skills of students with autism are being studied. The literature is analyzed, on the basis of which the main features of impaired communication abilities in schoolchildren with autism syndrome are identified. In the conditions of inclusive education, the problems of students with autism syndrome were generalized and identified.